1997
DOI: 10.1016/s0092-8674(00)80513-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Neuronal Intranuclear Inclusions Underlies the Neurological Dysfunction in Mice Transgenic for the HD Mutation

Abstract: Huntington's disease (HD) is one of an increasing number of human neurodegenerative disorders caused by a CAG/polyglutamine-repeat expansion. The mutation occurs in a gene of unknown function that is expressed in a wide range of tissues. The molecular mechanism responsible for the delayed onset, selective pattern of neuropathology, and cell death observed in HD has not been described. We have observed that mice transgenic for exon 1 of the human HD gene carrying (CAG)115 to (CAG)156 repeat expansions develop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

80
1,464
2
17

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,047 publications
(1,586 citation statements)
references
References 47 publications
80
1,464
2
17
Order By: Relevance
“…Thus the polyQ-length-dependent aggregation of HTTex1 in vitro mirrors observations in patients and in transgenic model systems [8,9].…”
Section: Pathogenic Polyq-containing Protein Aggregates In Patients Asupporting
confidence: 52%
See 2 more Smart Citations
“…Thus the polyQ-length-dependent aggregation of HTTex1 in vitro mirrors observations in patients and in transgenic model systems [8,9].…”
Section: Pathogenic Polyq-containing Protein Aggregates In Patients Asupporting
confidence: 52%
“…These aggregates, which are often concentrated in large inclusion bodies, are observed in brain regions that display massive neurodegeneration, suggesting that the process of polyQ-mediated protein misfolding and aggregation drives pathogenesis [8]. This hypothesis is supported by investigations in transgenic mouse, fly and worm models, which indicate that toxicity in neuronal cells correlates with the formation of polyQcontaining protein aggregates [9]. Moreover, in vitro studies with polyQ disease proteins have demonstrated that both spontaneous protein aggregation and toxicity are dependent on polyQ length.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although mtHtt lacks a nuclear localization signal, mtHtt can translocate to the nucleus and produce neurotoxicity in cell culture models. [101][102][103][104] Reportedly, the mtHtt/SNO-GAPDH/Siah1 complex translocates to the nucleus, enabling mtHtt to contribute to toxicity. 100 Supporting Figure 4 Possible mechanism of S-nitrosylated GAPDH (SNO-GAPDH) contributing to neuronal cell damage or death.…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…Characteristic neuropathological findings in SCA1 are the loss of Purkinje cells in the cerebellum and neurons in the inferior olivary complex (Robitaille et al, 1995). As described for other polyglutamine diseases such as Huntingdon's disease (HD) Davies et al, 1997), the presence of neuronal intranuclear inclusions (NIs) in Purkinje cells in human patients and in a transgenic mouse model (Skinner et al, 1997) represents a pathological hallmark of SCA 1. Recent evidence shows that compounds that increase inclusion formation might reduce cellular pathology in several neurodegenerative disorders (Bodner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%